ANALISIS HUKUM ISLAM TERHADAP KETENTUAN UPAH JURU PARKIR DALAM PERATURAN BUPATI NOMOR 12 TAHUN 2013 - Kharismatus Sa'dia; Achmad Yasin (Al-Aqad, 2025)
This research aims to analyze Regent Regulation (Perbup) No. 12 of 2013 concerning wages for parking attendants from an Islamic law perspective. The focus of the research is to see how the wage provisions for parking attendants are in accordance with Sharia principles, especially related to work contracts, fairness in providing proportional wages, and the protection of workers' rights in Islam. The research method used is a descriptive analytical approach by examining the Regional Regulations based on muamalah fiqh literature and other sources of Islamic law. The research results show that although Perbup No. 12 of 2013 provides clear regulations regarding wages for parking attendants, several aspects need to be reviewed further from a sharia perspective, such as clarity of contracts, fairness of proportional wages, as well as application of the principle of balancing rights and obligations between workers and employers. The implication of this study is the need for adjustments in local regulations to be more in line with the values ​​of justice and benefit taught in Islamic law, so as to create a wage system that is fairer and in line with sharia.